2018
DOI: 10.1037/lhb0000272
|View full text |Cite
|
Sign up to set email alerts
|

The single lineup paradigm: A new way to manipulate target presence in eyewitness identification experiments.

Abstract: The suspect in eyewitness lineups may be guilty or innocent. These possibilities are traditionally simulated in eyewitness identification studies using a dual-lineup paradigm: All witnesses observe the same perpetrator and then receive one of two lineups. In this paradigm, the suspect's guilt is manipulated by including the perpetrator in one lineup and an innocent suspect in the other. The lineup is then filled with people matched to either the suspect (resulting in different fillers in perpetrator-present an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 27 publications
(60 reference statements)
3
22
0
1
Order By: Relevance
“…1). Thus, the false-alarm rate should not vary as a function of filler similarity, consistent with prior results (10,16). Because the hit rate should increase but the false-alarm rate should remain constant as filler similarity decreases, the receiver operating characteristic (ROC) should reflect an improved ability to discriminate innocent from guilty suspects (17).…”
Section: Significancesupporting
confidence: 75%
“…1). Thus, the false-alarm rate should not vary as a function of filler similarity, consistent with prior results (10,16). Because the hit rate should increase but the false-alarm rate should remain constant as filler similarity decreases, the receiver operating characteristic (ROC) should reflect an improved ability to discriminate innocent from guilty suspects (17).…”
Section: Significancesupporting
confidence: 75%
“…In one of their two experiments they manipulated filler similarity relative to the suspect (i.e., using different fillers in target-present and -absent cases). Consistent with the original propositions of Luus and Wells (1991) and Wells et al (1993; see also Oriet & Fitzgerald, 2018)-that increasing filler similarity beyond matching to description risks affecting guilty but not innocent suspect identifications- Colloff et al (2021) reported a decrease in pAUC as filler similarity increased. They contrasted these results with a second experiment where filler similarity was manipulated relative to the target.…”
supporting
confidence: 76%
“…We used Oriet and Fitzgerald's (2018) We created eight versions of each lineup, in which we varied: i) the position of the suspect (position 2 or position 5); ii) the order of the fillers (order A-E or E-A); and iii) simultaneous or sequential presentation. For simultaneous lineups, the images were presented in a 2 × 3 array with a number from 1 to 6 beneath each image.…”
Section: Methodsmentioning
confidence: 99%